2019
DOI: 10.3390/app9122539
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Few-Layer Graphene Dispersions from Hydrothermally Expanded Graphite

Abstract: In this study, we propose a novel approach to prepare few-layer graphene (FLG) dispersions, which is realized by exfoliating natural graphite flakes in a surfactant aqueous solution under hydrothermal treatment and liquid-phase exfoliation. In order to obtain stable and well-dispersed FLG dispersions, pristine graphite is hydrothermally expanded in a hexadecyltrimethylammonium bromide (CTAB) aqueous solution at 180 °C for 15 h, followed by sonication up to 3 h. In comparison to long-time sonication methods, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…However, the q m = 121.95 mg g −1 is higher than previous studies (Table 4), suggesting that our green-prepared rGO is an excellent option for conventional materials. Although activated carbon seems to be more profitable to be used for the removal of MB [68] (Table 4), its adsorption equilibrium time (150 min) is higher compared to the present study (30 min), most importantly, rGO has a wide range of applications from composites to high frequency devices [21].…”
Section: Temperaturementioning
confidence: 55%
“…However, the q m = 121.95 mg g −1 is higher than previous studies (Table 4), suggesting that our green-prepared rGO is an excellent option for conventional materials. Although activated carbon seems to be more profitable to be used for the removal of MB [68] (Table 4), its adsorption equilibrium time (150 min) is higher compared to the present study (30 min), most importantly, rGO has a wide range of applications from composites to high frequency devices [21].…”
Section: Temperaturementioning
confidence: 55%
“…expanding the sonication time, raising the original concentration of graphite, introducing polymers, etc. In order to avoid graphene restacking during exfoliation, researchers have found that, with the aid of surfactants or dispersing agents, graphene sheets can be maintain in a good dispersion state after sonication …”
Section: D Graphene Synthesismentioning
confidence: 99%
“…Since the monolayer graphene was first obtained by Andre Geim and co-workers using the tape method [10], there has been increasing attention towards methods of such material preparation. The commonly applied methods include the micromechanical or chemical exfoliation of graphite, epitaxial growth on silicon carbide (SiC), chemical vapor deposition (CVD), as well as reduction of graphene oxide (GO) via chemical, electrochemical, thermal, or photocatalytic methods [11][12][13][14][15][16][17][18]. Among the above methods, a major focus of experimental research has been concentrated on the development of low-pollution preparation routes, enabling environmentally friendly production.…”
Section: Introductionmentioning
confidence: 99%